Risk governance framework on radiological emergency, preparedness and response for emergency responders based on a mixed methods study - Abd Rahman, Anita (2022)
Risk governance which encompasses processes and mechanisms as how decisions about risks are taken and implemented has become increasingly common, particularly in industries with established hazards. Nonetheless not much research explains risk practices and relation to governance in radiological emergency. Therefore, this study was conducted to determine influencing factors on emergency responder risk practices, exploring the view of governance founded on interviews and framing the overall governance in radiological emergency preparedness and response. A mixed methods study comprising of a cross-sectional study through self-administered questionnaire was conducted among 229 emergency respondents from related organisations. The qualitative approach adopted an in-depth interview from 6 purposedly sampled key informants. The quantitative analysis used multiple logistic regression to determine significant predictors. The qualitative data analysed transcripts via NVivo version 12 and through abductive coding, emerging themes were identified. Subsequently, both findings were converged to answer the research objectives and informed the development of a radiological risk governance framework. A total of 226 out of 229 respondents participated the questionnaire session, giving a response rate of 94.9 percent. The multiple logistic regression concluded seven independent variables with significant positive odds and was able to explain 57.9% of the variances for high score radiological risk practices. The variables were working in radiological related organisation (aOR=3.662, 95% CI: 1.147, 11.692; p=0.028), Risk Perception (aOR=1.170, 95% CI: 1.024, 1.338; p=0.021), Risk Management Proficiency (aOR=1.143, 95% CI: 1.037, 1.260; p=0.007), Decision Making (aOR=1.052, 95% CI: 1.001, 1.105; p=0.045), Evaluation on the Government (aOR=1.190, 95% CI: 1.100, 1.289; p<0.001), Cultural Values (aOR=1.176, 95% CI: 1.072, 1.291; p=0.001), and Risk in Context (aOR=1.061, 95% CI: 1.001, 1.127; p=0.049). For qualitative analysis, six themes emerged where structure, radiological plan, operation, risk management practices, governance and knowledge management represented in thematic network diagram. Lastly, both findings facilitated the framing of radiological risk governance relevant for emergency responders. Respondents from radiological related organisation had higher odds practices as their core business is specific into radiation related field. While more than two-third had high risk perception, only one third felt they were proficient in radiological risk management. This shows the need for continuous learning and training to further enhance responders understanding on potential hazards in an impacted area, how to protect people while optimizing the radiological best practices. More than two third of respondents would like to be involved in decision making as they are the one responding in actual event. Additionally, trust and evaluation of the government were important as this demonstrates leadership role. Interestingly, culture was also, and this can be seen from two angles, the cultural based on traditional value and from the organisation culture perspective. Therefore, the right culture to support risk management is an important ingredient for enhancing radiological risk practices. This study highlighted seven factors that influenced emergency responder risk practices in radiological EPR. Through data integration, it provided inputs for improvement on the existing risk practices and the diagrammatic radiological risk governance framework is hoped to be able to add further value in appreciating the overall findings.